Invasion History and Dispersion Dynamics of the Mediterranean Fruit Fly in the Balkan Peninsula - Mario Bjeliš; Vasilis G. Rodovitis; Darija Lemic; Pantelis Kaniouras; Pavao Gančević; Nikos T. Papadopoulos (Insects)
The Mediterranean fruit fly (medfly), Ceratitis capitata (Wiedemann 1824; Diptera, Tephritidae), is considered one of the most important pests, infesting more than 300 species of fresh fruit and vegetables worldwide. The medfly is an important invasive species, which has spread from the eastern part of sub-Saharan Africa to all of the world’s continents in recent centuries. Currently, the medfly is expanding its geographical range to cooler, temperate areas of the world, including northern areas of Mediterranean countries and continental areas of Central Europe. We collected and analysed all the available information, including in historical records, on the phenology of the medfly in the Balkan Peninsula, to map and understand the path of invasion and spread dynamics on the northern Mediterranean coast and in Central Europe. The medfly was first recorded in the Balkan Peninsula in 1915, in the Aegean area on the island of Aigina, followed by a few records on its presence in the Peloponnese in the early 1930s and throughout the Adriatic coastal area in the 1950s; it was first detected on the Croatian coast in 1947. By 2010, the medfly had been detected along the entire Ionian coast, while the first record of its presence on the Balkan coast of the Black Sea was made in 2005. Since 2000 to date, there has been a significant increase in the frequency of medfly detections in the interior of the Balkan Peninsula, including occasional detections in areas with unfavourable climatic conditions for overwintering, which seems to be favourable for reproduction during the summer and lead to significant infestation of late ripening fruits (late summer and autumn). In the last 20 years, the medfly has spread to more northerly areas (43 to 45 degrees latitude) and has been detected at higher altitudes (>200 to 600 m). Along the Balkan Peninsula, the infestation of fruits from 25 host plant species, from 14 genera and 10 plant families, has been reported. Considering the extremely high invasiveness of the medfly and its wide distribution in several Balkan regions with different climatic conditions, we can assume that it is adapting to new climatic conditions and infesting new host plants.